Desenvolvimento de um aplicativo móvel para controle de pré e pré e pós operatório de candidatos a cirurgia plástica - Camargos, Fabiano Andrade [UNIFESP] (2019)
Introduction: In the Brazilian Health System, patients are treated in poorly structured institutions to meet their psychosocial needs and health demands. Often, these patients can not answer their doubts because they do not have access to the professional, or they always return to different professionals, causing mismatched information, increasing doubts and causing preoperative quality of the procedure, which impairs the final result of the procedure. Objective: To develop a mobile App for better pre and postoperative control of patients who are candidates for plastic surgery. Method: To develop the application and the book in digital format, the doubts of the patients will be raised through the charts listing the main doubts of the patients during the pre and postoperative period. Results: With the improvement of the information we expect a lower rate of complications and cancellations of surgery, with this we will optimize the surgical block of the HJK contemplating a greater number of users and with this better serving the population .Conclusion: An App was developed for pre and postoperative control of plastic surgery candidates.